Substitution of C-terminus of VEGFR-2 with VEGFR-1 promotes VEGFR-1 activation and endothelial cell proliferation - Meyer, Rosana D (2004)
VEGFR-1 is devoid of ligand-dependent tyrosine autophosphorylation and its activation is not associated with proliferation of endothelial cells. The molecular mechanism responsible for this characteristic of VEGFR-1 is not known. In this study, we show that VEGFR-1 is devoid of ligand-dependent downregulation and failed to stimulate intracellular calcium release, cell migration and angiogenesis in vitro. To understand the molecular mechanisms responsible for the poor tyrosine autophosphorylation of VEGFR-1, we have either deleted the carboxyl terminus of VEGFR-1 or exchanged it with the carboxyl terminus of VEGFR-2. The deletion of carboxyl terminus of VEGFR-1 did not reverse its defective ligand-dependent autophosphorylation. The carboxyl terminus-swapped VEGFR-1, however, displayed ligand-dependent autophosphorylation, downregulation and also conveyed strong mitogenic responses. Thus, the carboxyl tail of VEGFR-1 restrains the ligand-dependent kinase activation and downregulation of VEGFR-1 and its ability to convey the angiogenic responses in endothelial cells.